Lo primero de la filosofía es conocer la absoluta nada” Fe y saber ante la cuestión del nihilismo (Revista Eletrônica Estudos Hegelianos, 2015)
The text analyzes the reading of the history of modern philosophy presented by Hegel in Faith and Knowledge in the light of the controversy triggered by Jacobi’s Spinozabriefe. The goal is to show that Faith and Knowledge is Hegel’s first answer to the Jacobian challenge and that it represents the first chapter of an interpretative parable that will find its final shape only in Hegel’s mature writings: if in the early Jena writings Hegel responds to the Jacobian conception of nihilism as destination of rationality, by showing that his reading is based on a concept of reason inheriting that which he seeks to criticize, and by presenting Spinoza as the key to deactivate such a reading, the Science of Logic accepts the Jacobian idea that philosophy is Spinozism. But presenting now his own philosophy as the true refutation of Spinozism, Hegel not only reverses the negative sign of nihilistic fate ascribed to rationalism by Jacobi, but also completes his reading of nihilism as an essential passage to philosophy: the nothing or the abyss of Spinoza’s substance is now «end», but at the same time «genesis of the concept», within which the dialectical transformation of Abgrund in Grund is performed.